76.3k views
5 votes
X-3y=-12; 2x+11y=-7 .algebra 2, elimination. I just need help solving

1 Answer

5 votes

The value of x is equal to -9.

The value of y is equal to 1.

x - 3y = -12

Add 3y to both sides.

x = -12 + 3y

Plug the value of x into the second equation.

2(-12 + 3y) + 11y = -7

Distributive property.

-24 + 6y + 11y = -7

Add 24 to both sides.

6y + 11y = 17

Combine like terms.

17y = 17

Divide both sides by 17.

y = 1

Now that we have the value of y we can plug it into the original equation to find the value of x.

x - 3(1) = -12

x - 3 = -12

Add 3 to both sides.

x = -9


User LukeS
by
4.9k points